2018
DOI: 10.1371/journal.pone.0205706
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine and phosphatidylethanolamine plasmalogens in lipid loaded human macrophages

Abstract: BackgroundPlasmalogens are either phosphatidylcholine (PC P) or phosphatidylethanolamine (PE P) glycerophospholipids containing a vinyl ether moiety in sn-1-position and an esterified fatty acid in sn-2 position. Multiple functions have been proposed, including reservoir of precursors for inflammatory mediators, modulation of membrane fluidity, and anti-oxidative properties. They could therefore play a role under conditions of metabolic stress. Especially enzymatically modified LDL (eLDL) and oxidatively modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 61 publications
1
23
0
1
Order By: Relevance
“…4) excluding ICC patients showed that lipids remained associated with genital inflammation independent from cancer. An increase in lipid metabolites from plasmalogens and long chain polyunsaturated fatty acids in ICC, not only indicate abnormality in cellular metabolism, but also highlight the significance of lipids in cancer development, due to their roles as precursors of pro-inflammatory cytokines, inducers of abnormal gene expression and ability to dysregulate cytokine production [65]. Interestingly, phosphatidylcholines, another group of lipids that positively correlated with genital inflammation, are typically known for their anti-inflammatory properties [66], but also contribute to cellular proliferation and programmed cell death [67].…”
Section: Discussionmentioning
confidence: 99%
“…4) excluding ICC patients showed that lipids remained associated with genital inflammation independent from cancer. An increase in lipid metabolites from plasmalogens and long chain polyunsaturated fatty acids in ICC, not only indicate abnormality in cellular metabolism, but also highlight the significance of lipids in cancer development, due to their roles as precursors of pro-inflammatory cytokines, inducers of abnormal gene expression and ability to dysregulate cytokine production [65]. Interestingly, phosphatidylcholines, another group of lipids that positively correlated with genital inflammation, are typically known for their anti-inflammatory properties [66], but also contribute to cellular proliferation and programmed cell death [67].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that CFTR alteration and disturbance of the membrane composition are somehow linked [62,63]. The increase in ether-link-bearing lipids may be a response to enhanced membrane stability [64]. In addition, it was suggested that ether lipids are involved in regulating cell differentiation, cellular signaling, and reducing oxidative stress by acting as endogenous antioxidants [65].…”
Section: Discussionmentioning
confidence: 69%
“…В частности, Lasareishvili B, et al [10], проведя исследования на 250 добровольцах, показали, что существуют положительные связи между числом LYM (преимущественно клетками CD4+ и CD8+) и концентрацией ОХС, ТАГ и ЛНП и отрицательные -между числом регуляторных Т-клеток (СD4+СD25+) и теми же показателями липидного обмена как у здоровых людей [10], так и больных с ожирением [11]. MON и макрофаги способны "насыщаться" и переносить различные липиды [12]. Показано, что у людей с нормальным и повышенным содержанием холестерина существуют…”
Section: Discussionunclassified